A Novel Minimal Invasive Mouse Model of Extracorporeal Circulation. (29th January 2015) - Luo, Shuhua; Tang, Menglin; Du, Lei; Gong, Lina; Xu, Jin; Chen, Youwen; Wang, Yabo; Lin, Ke; An, Qi
Abstract : Extracorporeal circulation (ECC) is necessary for conventional cardiac surgery and life support, but it often triggers systemic inflammation that can significantly damage tissue. Studies of ECC have been limited to large animals because of the complexity of the surgical procedures involved, which has hampered detailed understanding of ECC-induced injury. Here we describe a minimally invasive mouse model of ECC that may allow more extensive mechanistic studies. The right carotid artery and external jugular vein of anesthetized adult male C57BL/6 mice were cannulated to allow blood flow through a 1/32-inch external tube. All animals ( n = 2 0 ) survived 30 min ECC and subsequent 60 min observation. Blood analysis after ECC showed significant increases in levels of tumor necrosis factor α, interleukin-6, and neutrophil elastase in plasma, lung, and renal tissues, as well as increases in plasma creatinine and cystatin C and decreases in the oxygenation index. Histopathology showed that ECC induced the expected lung inflammation, which included alveolar congestion, hemorrhage, neutrophil infiltration, and alveolar wall thickening; in renal tissue, ECC induced intracytoplasmic vacuolization, acute tubular necrosis, and epithelial swelling. Our results suggest that this novel, minimally invasive mouse model can recapitulate many of the clinical features of ECC-induced systemic inflammatory response and organ injury.